Lewis acid Ni/Al-MCM-41 catalysts for H2-free deoxygenation of Reutealis trispermaoil to biofuels - Reva Edra Nugraha; Didik Prasetyoko; Hasliza Bahruji; Suprapto Suprapto; Nurul Asikin-Mijan; Titie Prapti Oetami; Aishah Abdul Jalil; Dai-Viet N. Vo; Yap, Taufiq Yun Hin (Royal Society of Chemistry, 2021)
The activity of mesoporous Al-MCM-41 for deoxygenation of Reutealis trisperma oil (RTO) was enhanced via modification with NiO nanoparticles. Deoxygenation at atmospheric pressure and under H2 free conditions required acid catalysts to ensure the removal of the oxygenated fragments in triglycerides to form liquid hydrocarbons. NiO at different weight loadings was impregnated onto Al-MCM-41 and the changes of Lewis/Brønsted acidity and mesoporosity of the catalysts were investigated. The activity of Al-MCM-41 was enhanced when impregnated with NiO due to the increase of Lewis acidity originating from NiO nanoparticles and the mesoporosity of Al-MCM-41. Increasing the NiO loading enhanced the Lewis acidity but not Brønsted acidity, leading to a higher conversion towards liquid hydrocarbon yield. Impregnation with 10% of NiO on Al-MCM-41 increased the conversion of RTO to hydrocarbons via the deoxygenation pathway and reduced the products from cracking reaction, consequently enhancing the green diesel (C11–C18) hydrocarbon products.